REPRESENTATION OF IDEOLOGY IN TEMPO NEWSPAPER ANCOL RECLAMATION NEWS DISCOURSE (Van Dijk Model Criticaldiscourse Analysis Study) - Arianty Visiaty; Yumna Rasyid; Miftahulkhairah Anwar (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2021)
ABSTRACT The study aims to examine the ideological representations that appear in the news in the media. The analysis of this research uses the CDA Van Dijk concept. The data of this research is the news entitled “DKI Mengklaim Perluasan Ancol untuk Publik” published in TEMPO Newspaper, Monday July 6, 2020. From the analysis, this news shows support for the reclamation policy of the Ancol area of the DKI Jakarta Government. Besides, it is known that this news represents the ideological strategy of capitalism. Keywords: Critical Discourse Analysis; Van Dijk model; ideology